On the processes of the charge transfer in the electrical conducting polymer materials - Marsagishvili, Tamaz; Aneli, Jimsher; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2013)
The analysis of charge transfer processes in the electrical conducting solid polymer systems has been carried out. The processes in these systems are divided to two types. The first type is the process of charge transfer between electrodes and particles while the second one – the process of the charge transfer between conductive particles. The description of medium is carried out using Green temperature functions of polarization operators for the molecular medium. It permits taking into account the effects of frequency and space dispersion. The analytical expressions for kinetic parameters of the charge transfer processes from electrodes to particles and between particles in condensed matter have been obtained. The comparison of the general theoretical dependence of the current in electric conducting polymer composites (ECPC) on the average distance between conducting particles with analogical dependence for some real ECPC are presented in the paper. Проведений аналіз процесів перенесення зарядів в твердих електропровідних полімерних системах. Процеси розділено на два типи: перший тип відноситься до процесу перенесення заряду від електродів на струмопровідні частинки, а другий – між цими частинками. Середовище описано за допомогою поляризаційних операторів функції Гріна для молекулярного середовища, що дає можливість враховувати частотні ефекти і просторову дисперсію. Одержано аналітичні вирази для кінетичних параметрів перенесення заряду від електродів на частинки і між частинками. Проведено порівняння результатів, отриманих теоретичними розрахунками залежності електроструму від середньої відстані між провідними частинками електропровідного полімерного композиту (ЕППК) з аналогічною залежністю, отриманою для реальних ЕППК.
Про процеси перенесення зарядів в електропровідних полімерних матеріалах
Keywords: polymer composite; charge transfer; vectorpotential; Hamiltonian; Green function; полімерний композит; перенесення заряду; вектор потенціалу; Гамільтоніан; функція Гріна